2022
DOI: 10.1186/s12981-021-00426-z
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity of personalized dendritic-cell therapy in HIV-1 infected individuals under suppressive antiretroviral treatment: interim analysis from a phase II clinical trial

Abstract: Background We developed a personalized Monocyte-Derived Dendritic-cell Therapy (MDDCT) for HIV-infected individuals on suppressive antiretroviral treatment and evaluated HIV-specific T-cell responses. Methods PBMCs were obtained from 10 HIV+ individuals enrolled in trial NCT02961829. Monocytes were differentiated into DCs using IFN-α and GM-CSF. After sequencing each patient’s HIV-1 Gag and determining HLA profiles, autologous Gag peptides were sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 84 publications
(80 reference statements)
0
4
0
Order By: Relevance
“…In contrast, certain studies have reported that this cytokine can increase the cytotoxic T lymphocytes and natural killer cell activities against HIV-1-infected cells. In addition, IFN-γ upregulates the MHC-II pathway supporting the antigen-specific activation of CD4 + T cells [24][25][26] . Research has exhibited that in primary HIV infection, ICAM-1 significantly increases and is involved in promoting inflammatory responses against HIV infection.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, certain studies have reported that this cytokine can increase the cytotoxic T lymphocytes and natural killer cell activities against HIV-1-infected cells. In addition, IFN-γ upregulates the MHC-II pathway supporting the antigen-specific activation of CD4 + T cells [24][25][26] . Research has exhibited that in primary HIV infection, ICAM-1 significantly increases and is involved in promoting inflammatory responses against HIV infection.…”
Section: Discussionmentioning
confidence: 99%
“…However, the discovery of the immunogenic capacity of DCs has been shown to be suitable for cancer therapy ( 20 ) and for other pathologies ( 21 ). In the last years, these immunogenic DCs have been used in personalized treatments in patients with HIV receiving antiretroviral treatment ( 22 ) or in ovarian cancer patients ( 23 ).…”
Section: Subsets and Their Role In Immunogenicitymentioning
confidence: 99%
“…This study was later withdrawn. Researchers in Sao Paolo launched a clinical trial toward HIV cure by studying a combination therapy involving Maraviroc and/or dolutegravir, dendritic cell vaccination, class III histone deacetylases (HDACs), surtuin-1, and auranofin to decrease the ratio of long-lived central memory/transitional memory (TTM) CD4+ T-cells. , Although results are not yet available, a positive outcome will result in an efficacious combination treatment regimen for HIV sterilizing cure.…”
Section: Therapeutic Gold Complexesmentioning
confidence: 99%